"I put my fingers around my throat and squeezed it, to know how it feels": Antigallows Sentimentalism and E. D. E. N. Southworth's The Hidden Hand - JONES, PAUL CHRISTIAN (Legacy (Amherst, Mass.), 2008)
A handful of studies have considered individual authors' interest in the subject, but the only scholar to have investigated the larger literary engagement with this movement is historian David Brion Davis.1 His description of the period's handling of capital punishment approaches what contemporary scholars label sentimentalism, although Davis himself does not use the term.2 For example, he claims that these writers yearned for an emotional and pietistic brotherhood, for an allinclusive love which would embrace the wayward murderer as well as the suffering slave and degraded drunkard, and pursued this aim by arous[ing]..